Neoadjuvant radiotherapy for retroperitoneal sarcoma: A systematic review. Issue 6 (16th March 2016) - Cheng, Hao; Miura, John T.; Lalehzari, Mona; Rajeev, Rahul; Donahue, Amy E.; Bedi, Meena; Gamblin, T. Clark; Turaga, Kiran K.; Johnston, Fabian M.
Abstract : Background and Objectives: The multi‐modal treatment of retroperitoneal sarcoma has seen increased use of neoadjuvant radiation. However, its effect on local recurrence and survival remain controversial. We aimed to synthesize and evaluate the literature. Methods: The review was conducted according the recommendation of the Meta‐Analysis of Observational Studies in Epidemiology (MOOSE) group with pre‐specified inclusion and exclusion criteria. Results: Of 8, 701 citations collected, 15 articles reported on 464 patients. The median age was 56 years (45–64). The predominant histological subtypes were liposarcoma (51.54%) and leiomyosarcoma (23.26%). Tumor differentiation composed of 37.1% well‐, 12.8% moderate‐, 46.0% poorly‐, and 4.1% undifferentiated. Most studies featured external beam radiation therapy (EBRT) treatment regimen with some who included patients treated with IMRT instead. Median follow‐up averaged 41.4 months (19–106 months). Median 5‐year OS, PFS, and LRR rates were 58%, 71.5%, and 25%. Using the NCI CTCAE, toxicities from Grade 1 (Mild) through Grade 5 (death) were experienced by 18.8%, 10.2%, 16.3%, 0.7%, and 1.6% of patients. Conclusions: NART is a safe to use for RPS, but its effect toward survival and local control remains unclear. Without randomized control trials, common reporting criteria for pro‐ and retrospective studies are needed to allow comparison between studies. J. Surg. Oncol. 2016;113:628–634 . © 2016 Wiley Periodicals, Inc.